(untitled) - Tolkien, J.R.R (New York, 1987)
To protect a magic ring, Frodo, the hobbit, must undertake a long and dangerous journey
Keywords: Fantasy fiction, English,Tiểu thuyết viễn tưởng Anh,Phim truyện,Wizards,Phù Thủy,Magicians,Feature films,Pháp sư; Drama,Phim,Drama,Phim